Anti-rancidity effect of essential oils, application in the lipid stability of cooked turkey meat patties and potential implications for health. (29th September 2014) - Loizzo, Monica R.; Tundis, Rosa; Menichini, Francesco; Duthie, Garry
Abstract: Twenty-three commercial essential oils were tested for their anti-rancidity effect and potential implications to prolong the induction time of corn oil and extend the shelf life of cooked turkey patties. Moreover, the potential health benefit was investigated through DPPH, ABTS, β-carotene bleaching, FRAP, and α-amylase inhibitory assays. Essential oils' composition was investigated by GC-MS. Cumin, thyme, clove, and cinnamon oils improved oxidative stability and increased the induction time of the corn oil 1.5–3 fold. Clove and cinnamon oils were particularly effective in delaying lipid oxidation of cooked turkey patties (time of induction 11.04 and 9.43 h) compared with the plain burger (5.04 h). Both oils are also characterized by a potent radical scavenging activity in ABTS test (IC50 values of 1.43 and 2.05 μg/ml for cinnamon and clove, respectively). In the α-amylase inhibitory assay, cumin and grape fruits were the most potent with IC50 values of 21.88 and 23.95 μg/ml, respectively.